النظام العام والآداب العامة في دستور جمهورية العراق ‏لعام 2005-دراسة تحليلية - majeed, Dr.Soz hameed (Journal of Legal and Political Studies, 2025)
The concept of "public order and morals" is one of the fundamental principles that govern modern societies, aiming to achieve a delicate balance between individual freedom and social responsibility. In modern constitutions, including the 2005 Constitution of the Republic of Iraq, these values and principles appear in various articles, reflecting their importance in maintaining societal stability and moral values. Public order and morals refer to a set of imperative rules and ethical standards designed to protect the interests and moral fabric of society. These are sometimes defined by explicit legal texts issued by the legislature, and in other cases, derived implicitly by the judiciary when necessary, guided by established social norms. Individuals become aware of these rules by consulting the official gazette, referring to published civil, criminal, and administrative legal texts, as well as judicial jurisprudence reflected in decisions and verdicts, in addition to scholarly references that explain their content and practical applications.This study addresses the concept of public order and morals as derived either from the preamble of the 2005 Constitution of the Republic of Iraq or from its explicit provisions. Keywords: Public order – Public morals – Constitution of the Republic of Iraq – Constitutional protection – Preamble of the Constitution.
Keywords: Keywords Public order Public morals Constitution of theRepublic of Iraq Constitutional protection Preamble of theConstitution